Determinants of tuberculosis in Central Region of Eritrea: a matched case-control study - Mebrahtu, Filmon G.; Ghezae, Meron M.; Below, Eden H.; Berhe, Daniel N.; Tesfamariam, Eyasu H.; Berhane, Tesfit N.; Sengal, Kiflu T.; Woldu, Henok G.; Teklemariam, Habtemichael M. (International Journal Of Community Medicine And Public Health, 2023)
Background: The WHO has recommended the need for holistic approach towards TB, including addressing the underlying socio-economic determinants in conjunction with direct observed treatment short-course (DOTS). However, there is lack of epidemiological data in Eritrea regarding factors that are associated with TB and this study aimed to assess such factors. Methods: A matched case-control study was used to assess factors that are associated with TB in the Central Region of Eritrea. A structured questionnaire was used to collect data about socio-demographic characteristics, living status, housing conditions, and medical history of the study participants. All TB patients in the eight DOTS treatment centers and two age-and-sex-matched controls for each case were included. Bivariate and multivariable conditional logistic regression models were used to identify the main risk factors of TB. Results: The study recruited 67 cases and 134 controls. Bivariate analyses indicated that BCG vaccination scar, past alcohol drinking habit, history of hospital admission, previous history of TB, and family history of TB were found to be factors associated with TB. Moreover, results of multivariable analysis showed that, absence of BCG vaccination scar, family history of TB, past drinking habit, and history of hospital admission were found to be factors associated with TB among the study participants. Conclusions: This is the first study in the Central Region of Eritrea that assessed the determinant of tuberculosis. Absence of BCG vaccination scar, family history of TB, past alcohol consumption and history of hospital admission were found to be independent risk factors for TB.c